The Effect of Indonesian EFL Senior High School Students’ Anxiety on Their Writing Achievement in Explanation Text - Kurniawati, Karisma; Anam, Syafi'ul (Makassar State University, 2023)
Abstract. Writing is considered to be one of the most challenging skills to learn. Accordingly, some issues appeared and may be faced by the students while writing. One of the writing issues that can be a serious problem is writing anxiety. Hence, in this study, the researcher tried to find out the eleven graders students' writing anxiety levels and investigate the significant difference of writing anxiety on students' writing achievement in an explanation text writing. This study used quantitative approach with ex-post facto research design. The researcher conducted this study at one of the public senior high schools in Gresik. There were 30 eleven graders taken as subjects from one class. Then, to gather the data, two instruments were used. First were the Second Language Writing Anxiety Inventory (SLWAI) close-ended questionnaires. Second was students' writing scores in an explanation text writing. To analyze the data, the researcher used both descriptive statistics and inferential statistics (ANOVA). The results found that the eleven grades’ students had a moderate level of writing anxiety. And the somatic anxiety was dominant had by them. Another result revealed that there is no significant difference in each type of writing anxiety on the students' writing achievement in explanation text. And only cognitive anxiety had a moderate size effect on the student's scores. So, based on this study, the writing anxiety did not influence whether the students succeed in their explanation text writing. Keywords: Writing Anxiety, Writing Achievement, Explanation Text